The Nazi past in contemporary German film : viewing experiences of intimacy and immersion - Bangert, Axel (Screen cultures., 2014)
From intimate portrayals of ordinary Germans and Nazi leaders to immersive spectacles of war and defeat, this study argues that, since 1990, German film has focused on portraying the Nazi past from within.